Anticonvulsant properties of methanol leaf extract of Laggera Aurita Linn. F. (Asteraceae) in laboratory animals. (15th September 2016) - Malami, S.; Kyari, H.; Danjuma, N.M.; Ya'u, J.; Hussaini, I.M.
Abstract: Ethnopharmacological relevance: Preparation of Laggera aurita Linn. (Asteraceae) is widely used in traditional medicine to treat various kinds of diseases such as epilepsy, malaria, fever, pain and asthma. Its efficacy is widely acclaimed among communities in Northern Nigeria. Aim of the study: The present study is aimed at establishing the possible anticonvulsant effects of the methanol leaf extract of Laggera aurita using acute and chronic anticonvulsant models. Materials and method: Median lethal dose (LD50 ) was determined in mice and rats via oral and intraperitoneal routes. Anticonvulsant screening of the extract was performed using maximal electroshock-induced seizure test in day-old chicks; pentylenetetrazole-, strychnine- and picrotoxin- induced seizure models in mice. Similarly; its effects on pentylenetetrazole-induce kindling in rats as well as when co-administered with fluphenamic and cyproheptadine in mice, were evaluated. Results: Median lethal dose (LD50 ) values were found to be >5000 mg/kg, p.o. and 2154 mg/kg, i.p., each for both rats and mice. The extract showed dose dependent protection against tonic hind limb extension (THLE) and significantly (p<0.05) decreased the mean recovery from seizure in the maximal electroshock-induced seizure. In the pentylenetetrazole-induced seizure model, the extract offered 50% protection at 600 mg/kg and also increased the mean onset of seizure at all doses with significant (p<0.05) increase at the highest dose (600 mg/kg). Similarly the extract produced significant (p<0.05) increase in the onset of seizures in both strychnine- and picrotoxin- induced seizure models, at all the doses except at 150 mg/kg for the picrotoxin model. Co-administration of fluphenamic acid (FFA) (5 mg/kg) and the extract (600 mg/kg) showed an enhanced effect with percentage protection of 70% while co-administration of FFA (5 mg/kg) and phenytoin (5 mg/kg) as well phenytoin (5 mg/kg) and the extract (600 mg/kg) produced an additive effect. Administration of the extract (600 mg/kg), phenytoin (20 mg/kg) and cyproheptadine (4 mg/kg) offered 40%, 100% and 0% protection against THLE, each respectively, while co-administration of cyproheptadine (4 mg/kg) and the extract (600 mg/kg) as well as co-administration of cyproheptadine (4 mg/kg) and phenytoin (20 mg/kg) offered reduced protection of 20% and 50% each respectively. The extract at all doses reduced the severity of seizure episodes induced by PTZ-induced kindling. Conclusion: The results suggest that the methanol leaf extract of Laggera aurita possesses anticonvulsant and antiepileptogenic properties. Graphical abstract: The anticonvulsant effects of methanol leaf extract of Laggera aurita were investigated and found to possess antiepileptic and antiepileptogenic properties in animals. Thus, scientifically validate the folkloric use of the plant in the management of epilepsy.